2019
DOI: 10.1177/2156759x20903013
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for School Counselors: Applying the Multicultural and Social Justice Counseling Competencies (MSJCC) in Assisting Korean Adolescent Students in the United States

Abstract: The school counseling profession strongly encourages practitioners to work within a multicultural and a social justice perspective. More literature is needed that clarifies exactly how school counselors can use such a perspective in working with Asian student populations. We describe how school counselors can use the Multicultural and Social Justice Counseling Competencies framework in school counseling with the rapidly growing Korean adolescent student population in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…At this point, school counselor have to also develop their multicultural competence, primarily in dealing with counselees from specific populations, such as the Indonesians. Some studies have reported that the key success of a counselor is their ability to work with students from various backgrounds professionally, so counselors have to constantly expand their multicultural competence and get away from the white people's framework of thinking (west culture) (Dowden, Anderson, & Mccloud, 2021;Singh, Appling, & Trepal, 2020). It is caused by the counselee's developed issues and cultural considerations during the counseling process (Bjornestad, Mims, & Mims, 2016;Finnerty, Luke, & Duffy, 2019;Ohrt, Blalock, & Limberg, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…At this point, school counselor have to also develop their multicultural competence, primarily in dealing with counselees from specific populations, such as the Indonesians. Some studies have reported that the key success of a counselor is their ability to work with students from various backgrounds professionally, so counselors have to constantly expand their multicultural competence and get away from the white people's framework of thinking (west culture) (Dowden, Anderson, & Mccloud, 2021;Singh, Appling, & Trepal, 2020). It is caused by the counselee's developed issues and cultural considerations during the counseling process (Bjornestad, Mims, & Mims, 2016;Finnerty, Luke, & Duffy, 2019;Ohrt, Blalock, & Limberg, 2016).…”
Section: Introductionmentioning
confidence: 99%